2021
DOI: 10.3389/fnut.2021.680241
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli Florets Supplementation Improves Insulin Sensitivity and Alters Gut Microbiome Population—A Steatosis Mice Model Induced by High-Fat Diet

Abstract: Nonalcoholic fatty liver disease (NAFLD) is linked to obesity, type 2 diabetes, hyperlipidemia, and gut dysbiosis. Gut microbiota profoundly affects the host energy homeostasis, which, in turn, is affected by a high-fat diet (HFD) through the liver-gut axis, among others. Broccoli contains beneficial bioactive compounds and may protect against several diseases. This study aimed to determine the effects of broccoli supplementation to an HFD on metabolic parameters and gut microbiome in mice. Male (7–8 weeks old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
0
11
1
Order By: Relevance
“…Diet-induced obese mice can develop liver fatty changes, a condition also referred to as hepatic steatosis, that can be alleviated by broccoli, glucoraphanin or broccoli microgreens juice supplementation (22,34,36,37,39). However, another study using broccoli florets or stalks in diet-induced obese mice reported no changes in hepatic steatosis (38). In our study, the WD group showed mostly diffuse liver fatty changes, which was significantly different from the CTR group.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Diet-induced obese mice can develop liver fatty changes, a condition also referred to as hepatic steatosis, that can be alleviated by broccoli, glucoraphanin or broccoli microgreens juice supplementation (22,34,36,37,39). However, another study using broccoli florets or stalks in diet-induced obese mice reported no changes in hepatic steatosis (38). In our study, the WD group showed mostly diffuse liver fatty changes, which was significantly different from the CTR group.…”
Section: Discussioncontrasting
confidence: 73%
“…Moreover, the oral administration of broccoli microgreens juice, at a dose of 20 g/kg/day, reduced body weight, white fat mass and liver fat in HFD-fed mice (37). Conversely, the ingestion of broccoli florets (10%) or stalks (10%) for 17 weeks, by mice fed with HFD did not affect final body weight, fat accumulation or liver weight (38). In another study, for mice fed a Western diet with 10% broccoli powder (equivalent to 0.4 mmol glucoraphanin/kg diet) for 31 weeks, the final body weight was not affected by broccoli supplementation (39).…”
Section: Discussionmentioning
confidence: 91%
“…On the 16th week, an oral glucose tolerance test (OGTT) was performed in overnight (12 h) fasted mice as previously described ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…#EZRMI–13K). Homeostatic model assessment for insulin resistance (HOMA-IR) index was calculated as previously described ( 14 ). Plasma FFA was determined using an Abcam Free Fatty Acids Quantification Assay Kit (ab65341) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Liver tissue lysates were prepared using lysis buffer as previously described [ 23 ]. Aliquots of protein were then subjected to western blot analysis.…”
Section: Methodsmentioning
confidence: 99%